Analysis and Simulation of Workspace of Dual-arm Robot - Xie Shengliang; Liu Zuoshi (Jixie chuandong)
Taking the dual-arm robot as the research object and its workspace is analyzed. Firstly,the D-H method is used to establish the linkage coordinate system of the dual-arm robot and the forward kinematics equation is solved. Then,the 3 D workspace is solved based on the Monte Carlo method,which be stratified along the Z-axis direction. Thirdly,the method of partitioning by angle and the extreme value theory are used to extract the boundary points of the workspace. Finally,the least square method is applied to fit the boundary points. The results from the MATLAB simulation show that the extraction effect of boundary points is better,the error of fitting curve is smaller and the cooperation space of the dual-arm robot is larger,which provides a reference value for the dynamics analysis,trajectory planning and motion control of the dual-arm robot.